Study and Dimensioning of the Tanks Dedicated to a Compressed Air Storage System (CAES) - Ilham Rais; H. Mahmoudi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The fundamental idea of storage is to transfer available energy During periods of low demand, using only a fraction of the fuel that would be consumed by the standard production machine (gas turbine, thermal engine, etc.). The main role of energy storage is therefore to introduce an energy degree of freedom to decouple Consumers and the producer by supplying or Delivering the difference between these two powers. In this paper is this paper presents a brief study and dimensioning of compressed air storage tanks to a hybrid system wind-PV . adopts the CAES system as a storage agent. Starting with the technical criteria on which the choice of reservoirs is based and the mechanical constraints that must be taken into consideration for dimensioning of the reservoirs